Brewing unit time series analysis in the research of the complex system attractor properties - Чернецький, Микола Володимирович; Кишенько, Василь Дмитрович (Eastern-European Journal of Enterprise Technologies, 2014)
We have studied time series of a grout technology in making beer wort on the basis of grout temperature time series, using non-linear dynamics methods. We have developed algorithms for studying complex dynamic management systems as well as reconstructed attractors due to historical data on a brewing unit operation. Ultimately, we have estimated the Hurst index, the fractal volume, the delay time, the maximum phase space, and the correlation format. Our analysis of the indices has determined that the technological process of making beer wort has a complex non-linear behavior. This requires adequate methods and systems of synergetic management, which would be compatible with the physical nature of the object. This approach allows using natural mechanisms of the beer wort technology at full capacity, which saves energy and expenses.